Cover Feature: Molecular Cage Assembly by Sn−O−Sn Bridging of Di‐, Tri‐ and Tetranuclear Organotin Tectons: Extending the Spacing in Double Ladder Structures (Chem. Eur. J. 48/2021). Issue 48 (6th August 2021) - Rojas‐León, Irán; Gómez‐Jaimes, Gelen; Montes‐Tolentino, Pedro; Hiller, Wolf; Alnasr, Hazem; Rodríguez‐Molina, Braulio; Hernández‐Ahuactzi, Irán F.; Beltrán, Hiram; Jurkschat, Klaus; Höpfl, Herbert
Abstract : In a cooperative effort between research groups from Dortmund (Germany, coat of arms on the left) and Cuernavaca (Morelos, México, coat of arms on the right), novel molecular cages were synthesized and characterized by state‐of‐the‐art analytical methods and DFT calculations. Among these novel compounds, the spacer‐bridged tetraorganodistannoxane in the centre showing a double‐ladder structure exhibits a record spacing between the opposite tin centres. More information can be found in the Communication by K. Jurkschat, H. Höpfl, et al. (DOI: 10.1002/chem.202101055 ).